2020
DOI: 10.7759/cureus.11803
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of a Super Morbidly Obese Obstetric Patient With a Body Mass Index of 109 kg/m2 Presenting for Her Fourth Caesarean Delivery

Abstract: Morbidly obese obstetric patients undergoing anesthesia present many unique challenges. Previous caesarean sections (CSs) further complicate their management. We present the successful anesthetic management of a super morbidly obese obstetric patient with body mass index (BMI) of 109 kg/m 2 who underwent her fourth CS. As per our review, this patient has the highest recorded BMI in the obstetric anesthesia literature. A 27-year-old female, G4P3003, presented for fourth repeat CS at 38 weeks' gestation. She had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thromboembolism also can be a cause of cardiac arrest in the peripartum period and is a significant concern for obese parturients [ 10 ]. Reports have demonstrated cases of cardiac arrest resulting from pulmonary embolism in morbidly obese parturients during the perioperative period [ 11 , 12 ]. Given the absence of thromboprophylaxis in our patient, thromboembolism should be considered as a potential differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolism also can be a cause of cardiac arrest in the peripartum period and is a significant concern for obese parturients [ 10 ]. Reports have demonstrated cases of cardiac arrest resulting from pulmonary embolism in morbidly obese parturients during the perioperative period [ 11 , 12 ]. Given the absence of thromboprophylaxis in our patient, thromboembolism should be considered as a potential differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient suffered a massive pulmonary embolism, leading to intraoperative cardiac arrest. In a recent case report, a patient with a BMI of 109 kg/m 2 who underwent a cesarean delivery also had a history of cardiac arrest from a pulmonary embolism in a previous delivery [ 36 ]. These two cases highlight that parturients with obesity have higher risks from anesthesia and cardiac arrest in the peripartum period than pregnant women of normal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDPH is a potential risk, studies suggest that PDPH may be reduced among those with BMI >30 [ 18 , 19 ]. Incidence of PDPH in patients with BMI very much higher than 50 remains unstudied, although no PDPH has occurred in any of the cases of cesarean patients with BMI >70 as reported in the literature [ 8 - 11 ]. The mechanism of lowered risk is uncertain, but theories proposed include increased abdominal pressure or epidural lipomatosis possibly compressing the intrathecal space and reducing leakage [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus as to whether risks rise continuously, plateau, or show an inflection point as BMI rises above 40. Our literature review has revealed only a single case report discussing general anesthesia during a repeat cesarean delivery in a woman with BMI >100, and three case series discussing five cesarean patients with BMI ranging from 70 to 90 [8][9][10][11]. In this report, we describe the anesthetic management of a patient with a BMI >100 during consecutive cesarean deliveries, focusing on considerations unique to cases with this level of obesity.…”
Section: Introductionmentioning
confidence: 99%